Sclerotium rolfsii에 의한 꽃향유 흰비단병 발생 - 권진혁(Jin-Hyeuk Kwon); 박창석(Chang-Seuk Park) (Sigmulbyeong yeon'gu, 2008)
From 2006 to 2007, the stem rot of Elsholtzia splendens Nakai caused by Sclerotium rolfsii occurred sporadically in an herbs exhibition at Gyeongsangnam-do Agricultural Research and Extension Services, Korea. The typical symptom is water-soaking, dark brown on the stem and rotting, wilting and blighting. The infected plants were mostly died. White mycelial mats were spread over lesions, and then sclerotia were formed on stems and near soil line. The sclerotia were globoid in shape, $1{\sim}3$ mm in size and white to brown in color. The optimum temperature and sclerotia on PDA was $30^{°}C$ and the hyphal width was $4{\sim}9μ$. The typical clamp connections were observed in the hyphae of the fungus grown on PDA. On the basis of mycological characteristics and pathogenicity to host plants, this fungus was identified as Sclerotium rolfsii Saccardo. This is the first report on the stem rot of E. splendens caused by S. rolfsii in Korea. 2006과 2007년 2년간 경상남도농업기술원 약초 전시포장에 재배중인 꽃향유에서 S. rolfsii에 의한 흰비단병이 발생되었다. 병징은 줄기와 지제부위가 수침상으로 물러지고 부패하면서 암갈색으로 시들어 말라 죽는다. 병반부와 지제부위의 토양 표면에 흰색의 곰팡이가 솜털처럼 생기고 감자한천 배지에서 갈색의 둥근 균핵을 많이 형성하였으며 크기는 $1{\sim}3mm$였다. 균사의 폭은 $4{\sim}9μ$이며 균사생육 적온은 $30^{°}C$였으며 균사특유의 clamp connection이 관찰되었다. 꽃향유에서 발생한 병징과 균학적 특징 및 병원성을 검정한 결과, 이 병을 Sclerotium rolfsii Saccardo에 의한 꽃향유 흰비단병으로 명명하고자 한다.